Principles of Good Design: A Guide for Developing Visual Identities - Díaz-Mesa, Haridian (Ardin. Arte, Diseño e Ingeniería, 2025)
Graphic design plays an essential role in visual communication, especially in branding. However, the lack of unified criteria and prevailing subjectivity complicate objective design evaluation, ultimately affecting the quality and performance of brands. This article aims to establish principles of Good Design applicable to the creation of visual identities. A qualitative, exploratory methodology was employed, involving a focus group of experts in graphic design and corporate visual identity. The focus group identified three core dimensions of Good Design: ethics, aesthetics, and functionality, each further detailed through criteria such as originality, accessibility, durability, and simplicity, among others. The findings reveal that Good Design in the ethical dimension should promote social and environmental responsibility; in the aesthetic dimension, it should be aligned with the values of the issuer; and in the functional dimension, it should ensure clear and effective communication. In conclusion, this paper proposes a framework of criteria to guide designers and brand managers in the evaluation and creation of visual identities. While not guaranteeing perfect solutions, these principles provide a sound basis for reducing risks and encouraging ethical and responsible practices. Periodic review is recommended to adapt them to changing design needs and contexts.